A Case of Methotrexate Neurotoxicity Presented as Status Epilepticus, Encephalopathy, and High Fever. (July 2019) - Ayalon, Itay; Friedman, Shirley; Binenbaum, Yoav; Oppenheimer, Noga; Shiran, Shelly; Grisaru-Soen, Galia; Uliel-Sibony, Shimrit; Glatstein, Miguel; Kaplan, Jennifer Melissa; Sadot, Efraim
High-dose methotrexate is used to treat a range of adult and childhood cancers including osteosarcoma. Significant neurotoxicity is reported in 1% to 4.5% of patients treated with high-dose methotrexate and can present in a wide variety of symptoms. We present a case of a 14-year-old boy with a recent diagnosis of osteosarcoma who presented to the emergency department with status epilepticus, altered mental status, and very high fever secondary to methotrexate neurotoxicity. We review current literature and discuss some controversies related to this state. We also describe high fever as one of the possible symptoms associated with this condition and suggest using specific magnetic resonance imaging sequence to uncover abnormal findings related to this state. Since high-dose methotrexate is not a rare treatment in this era, we believe that in addition to oncologists, emergency department and intensive care providers should be aware of the potential role of methotrexate in causing significant neurotoxicity and include it in the differential diagnosis when treating a patient presenting with new neurological symptoms in the setting of recent high-dose methotrexate treatment.